2002
DOI: 10.1258/0022215021910014
|View full text |Cite
|
Sign up to set email alerts
|

Congenital conductive hearing loss

Abstract: Congenital conductive hearing loss due to ossicular deformities can be treated by either rehabilitation with a hearing aid or surgical reconstruction. We present the results of exploratory tympanotomy performed in a large paediatric otolaryngology centre in 67 patients with non-serous congenital conductive hearing loss. Forty-two children had malformation of one or more ossicles without fixation of the stapes, and 19 had fixed stapes. In 26 cases, the surgeon decided not to perform surgical correction. Seven o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 14 publications
(19 reference statements)
3
45
0
Order By: Relevance
“…The stapes footplate fixation malformation (class I according to the Teunissen and Cremers classification) is thought to be the most common isolated middle ear anomaly and has been the subject of serial analyses more frequently than any other category of anomalies [Teunissen et al, 1990;Hashimoto et al, 2002;Raveh et al, 2002;Hung et al, 2003;. Similar to the observations of Kojima et al , ossicular malformations associated with a mobile footplate were predominant (57.6%) in our study, while stapes fixation was found in 24.2% of cases and stapes fixation with other ossicular malformations in 18.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The stapes footplate fixation malformation (class I according to the Teunissen and Cremers classification) is thought to be the most common isolated middle ear anomaly and has been the subject of serial analyses more frequently than any other category of anomalies [Teunissen et al, 1990;Hashimoto et al, 2002;Raveh et al, 2002;Hung et al, 2003;. Similar to the observations of Kojima et al , ossicular malformations associated with a mobile footplate were predominant (57.6%) in our study, while stapes fixation was found in 24.2% of cases and stapes fixation with other ossicular malformations in 18.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they are clinically important because hearing loss can be corrected by an appropriate procedure. The most common congenital isolated ossicular anomalies are stapes fixation and incudostapedial discontinuity [14]. Several authors report the prevalence of isolated congenital stapes fixation between 20 and 35 % of ossicular malformations [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Jahrsdoerfer [3] reported a large series of 50 operated cases of minor congenital malformations of the ear, but none of these had similar abnormalities to the present case. Raveh et al [4] reviewed the charts of 416 children who underwent tympanotomy between 1986 and 1996 in the Hospital for Sick Children in Toronto, a large tertiary referral center. Sixty-seven of these were operated for congenital conductive hearing loss of unknown origin.…”
Section: Discussionmentioning
confidence: 99%